2014
DOI: 10.18404/ijemst.72106
|View full text |Cite
|
Sign up to set email alerts
|

Positive Emotion in Nature as a Precursor to Learning

Abstract: This study was designed to examine the perception of learning in adults generated by the effect of a positive emotion-in this case, awe. For the study, a working definition of awe is an impact-provoking reverence due to a powerful, positive emotional response to the natural world. This qualitative study used primarily face-to-face interviews. A total of 71 adults were interviewed and 113 interviews were conducted. These adults described an experience in which they felt impacted by awe and as a result perceived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
1
4
0
1
Order By: Relevance
“…Like others, we propose that awe might be a particularly potent catalyst for learning-and for science learning, in particular (Coleman, 2014;Valdesolo, et al, 2017). Expectancy violations have been shown to stimulate learning in both children and adults (Lorini & Castelfranchi, 2007;Stahl & Feigenson, 2015), and awe translates expectancy violations and knowledge gaps into scientific interest (McPhetres, 2019), thus motivating learning.…”
Section: Theoretical Frameworksupporting
confidence: 59%
See 2 more Smart Citations
“…Like others, we propose that awe might be a particularly potent catalyst for learning-and for science learning, in particular (Coleman, 2014;Valdesolo, et al, 2017). Expectancy violations have been shown to stimulate learning in both children and adults (Lorini & Castelfranchi, 2007;Stahl & Feigenson, 2015), and awe translates expectancy violations and knowledge gaps into scientific interest (McPhetres, 2019), thus motivating learning.…”
Section: Theoretical Frameworksupporting
confidence: 59%
“…This facet of awe is understudied, but these findings might be less surprising than they seem at first glance. The assumption underlying our research and clearly explicated elsewhere (Coleman, 2014;Valdesolo et al, 2017;Gottlieb et al, 2018;McPhetres, 2019) is that awe promotes engagement and learning. However, giving careful consideration of the "chills" indicators raises the possibility that the awe-engagement association may depend on the interaction of facet and timescale.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Tutumun yanı sıra farklı duyuşsal değişkenlerin de incelenmesi gereklidir. Nitekim araştırmalar aracılığıyla elde edilen bulgular, öğrencilerin eğitim ortamlarında hissettikleri başarıyla ilgili duyguların ve bilgiye yönelik meraklarının öğrenme sürecinin hem niceliğiyle hem de niteliğiyle yakından ilişkili olduğunu göstermiştir (Coleman, 2014;Litman & Jimerson, 2004;Pekrun, 2006). Ancak, alanyazında duygular ve bilgiye yönelik merakın, İngilizce ders başarısıyla ilişkilerinin incelendiği bir çalışmaya rastlanmamıştır.…”
Section: Türkçe Sürüm Girişunclassified
“…In addition to the attitude variable, which is focused in these studies, it is also necessary to examine different affective variables. Indeed, the findings obtained in previous studies showed that the feelings of the students about their success in learning environments and their epistemic curiosity are closely related to both the quantity and the quality of the learning processes (Coleman, 2014;Litman & Jimerson, 2004;Pekrun, 2006). However, there are no studies conducted on the relationship between emotional and epistemic curiosity and the success of English classes.…”
Section: Introductionmentioning
confidence: 99%